2019
DOI: 10.1016/j.jneb.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Using Theory to Evaluate the Implementation and Integration of an Expanded School Breakfast Program in Rural Midwestern High Schools

Abstract: Normalization Process Theory can be used to evaluate the implementation, embedding, and integration of a modified SBP into a school program. This evaluation can support other schools in modifying and embedding their SBPs into their school environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Adding factor integration to the model also enhanced fit. In the present study, it was defined as “the extent to which the approach is part of school routines, norms, and identity.” Previous studies have suggested similar dimensions, mainly as an indicator of program sustainability 8,73 . While integration may be conditional for sustaining the program, the authors argue that it is more related to the extent to which the program is “added‐in” to the school system (rather than “added‐on”) 29,47 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adding factor integration to the model also enhanced fit. In the present study, it was defined as “the extent to which the approach is part of school routines, norms, and identity.” Previous studies have suggested similar dimensions, mainly as an indicator of program sustainability 8,73 . While integration may be conditional for sustaining the program, the authors argue that it is more related to the extent to which the program is “added‐in” to the school system (rather than “added‐on”) 29,47 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested similar dimensions, mainly as an indicator of program sustainability. 8,73 While integration may be conditional for sustaining the program, the authors argue that it is more related to the extent to which the program is ''added-in'' to the school system (rather than ''added-on''). 29,47 Further research is needed to accumulate evidence for the relation with other dimensions, and indicators of integration.…”
Section: Fidelity Adaptation and Integrationmentioning
confidence: 99%